Jejak Trauma dan Memori Kolektif dalam Cerpen Serpihan yang Terbuang: Pendekatan Semiotik Peirce - Siti Rahmawati; Waeni Waeni; Yuliana Rosmawati; Rendi Ferdiansyah; Rusli Rusli (Jurnal Bahastra, 2026)
This study aims to reveal the meaning and narrative structure of the short story Serpihan yang Terbuang by Tin Miswary through Charles Sanders Peirce’s semiotic approach. The research addresses how signs—icons, indices, and symbols—construct semiosis in representing traumatic experiences, memory, and collective history. The narrative centers on Amad Bh’eng, a scavenger who preserves ordinary objects as repositories of personal and social memory, including the loss of family and past life experiences. Employing a qualitative descriptive method with textual analysis, the study identifies icons through sensory representations such as visual imagery, sound, and smell; indices through causal relationships between objects and the character’s memories; and symbols through objects that embody emotional and historical meanings. The findings demonstrate that the story’s meaning emerges from the dynamic interaction between sign, object, and interpretant, whereby mundane objects function as powerful markers of life, trauma, and collective memory. This study contributes a novel perspective by applying Peirce’s semiotic framework to contemporary short fiction, an approach that remains relatively underexplored.